About a rare cause of calf pain in an athlete: the popliteal artery entrapment syndrome. Issue 6 (30th June 2021) - Abcha, Oussama; Ammar, Ameni; Daghfous, Mohamed Samir
Introduction: Subsequent pain after a central ligament injury of the knee is usually attributed to meniscal or osteochondral damage inherent in trauma or secondary to knee instability. It has not been reported that vascular calf pain can be triggered by knee ligament trauma. Methods: We report a rare case of popliteal artery entrapment syndrome (PAES), discovered during a vascular claudication following post-traumatic anterior instability of the knee. The diagnosis was confirmed by CT angiography which showed a PAES, with a pathway in the inter-condylar notch. The patient had a releasing of the trapped vessel by myomectomy, with disappearance of vascular symptoms six months later. Results: Through this case, we wanted to draw the attention of orthopedic surgeons to the fact that the PAES can be asymptomatic. Its symptomatology can be triggered by a traumatic instability of the knee. Its presence represents a risk of lesion of the popliteal artery during arthroscopic ACL reconstruction. Therefore, it is important to think about this disease if a calf pain occurring after a ligament injury of the knee.